Students’ Perception on The Use of Note taking Strategy in Listening Academic Purposes - Mokobombang, Vidya Firka; Sambouw, Elsje L.; Badu, Helena (Pascasarjana, Universitas Negeri Gorontalo, 2024)
A note-taking strategy is crucial for students to understand the meaning of the conversations or audio they are listening to. Therefore, the researcher conducted this research to know how the students' perceptions about the use of note-taking strategy in listening for academic purposes. In this research, a questionnaire and an interview are used as the technique of data collection. The participants of this research are the students of the English department in the fourth semester of the academic year 2018-2019.Â The sample of the research is 21 students who were selected randomly. The result of this research shows that the students have a good perception of the use of note-taking strategy in listening subjects. They use a note-taking strategy in listening subject in order to understand and remember every important point of the information that is heard. In addition, many advantages can be found in the process of using a note-taking strategy in listening subjects, such as they can remember the information, get the main point and review the material they have learned before.Â